O professor e intelectual Kabengele Munanga no Brasil: observações sobre identidades, etnia, raça e políticas sociais - Reinaldo José de Oliveira; Regina Marques de Souza Oliveira (IdeAs)
The purpose of this text is to present the history and the historical, social, cultural and political trajectory of professor and intellectual Kabengele Munanga. For 32 years, our interlocutor dedicated himself to academic and social work at the Faculty of Social Sciences at the University of São Paulo. For more than three decades, intellectual and social production has focused on the production of researchers and teachers, in particular, young black men and women, the elaboration of literature on ethnic racial relations, and the production of reflections and actions along with the black social movement. Over the past 50 years, the partition of our interlocutor is essential for the fight against racism and the development of ideas, concepts and reflections on ethnic racial relations and the construction of citizenship.